2021
DOI: 10.3389/fpsyg.2021.662265
|View full text |Cite
|
Sign up to set email alerts
|

Home Literacy and Numeracy Interact and Mediate the Relationship Between Socio-Economic Status and Early Linguistic and Numeracy Skills in Preschoolers

Abstract: This longitudinal study aimed at evaluating the relationships between socio-economic status (SES) and early literacy and numeracy skills, testing home literacy and home numeracy as mediators. It also investigated the interaction of home literacy and numeracy on early literacy and numeracy skills. The study involved 310 preschool children attending the second and the third year. Parents completed questionnaires on SES and home literacy and numeracy. In the first session, children were administered language meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 111 publications
(186 reference statements)
3
14
0
Order By: Relevance
“…However, it has to be underlined that there was a significant interaction time*group in nonword reading speed, where low-SES monolinguals started from a lower level of performance and showed a considerable increase compared to the other group. For this group, we might speculate that the Low-SES condition might have impacted a poorer home literacy environment, which is connected to early linguistic and literacy skills [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has to be underlined that there was a significant interaction time*group in nonword reading speed, where low-SES monolinguals started from a lower level of performance and showed a considerable increase compared to the other group. For this group, we might speculate that the Low-SES condition might have impacted a poorer home literacy environment, which is connected to early linguistic and literacy skills [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, parents' level of instruction and profession may mediate access to different living conditions, as well as different exposures to verbal exchanges and involvement in dialogues and reading experiences. Previous evidence found that, in the Italian context, SES was related to early literacy skills in monolingual populations, and it was mediated by home literacy and numeracy activities [5]. Therefore, the differential influence of sequential bilingualism and SES on literacy development needs to be better investigated.…”
Section: Introductionmentioning
confidence: 97%
“…Consequently, children may lack reading materials, thus, undermining their ability to develop the required reading habits. As such, children from lower socio-economic backgrounds may find the reading less enjoyable compared to their peers from high social economic status (Bonifacci et al, 2021). Naite (2021) affirms that parents' education level, age, employment and marital status had a great impact on their children's education.…”
Section: Parental Factors Determining Children's Competences In Liter...mentioning
confidence: 91%
“…In the second approach, researchers perceive the HLE as more content-specific and focused on elements that promote literacy and numeracy. The content-specific approach includes various dimensions of the HLE for example the home literacy environment (Rose et al, 2018), the home numeracy environment (Manolitsis et al, 2013;Bonifacci et al, 2021), and the home digital environment (Sonnenschein et al, 2021).…”
Section: Defining the Home Learning Environmentmentioning
confidence: 99%
“…The quality of the early HLE is also associated with longterm effects on children's literacy and numeracy competencies and their academic achievement (Niklas and Schneider, 2017). Several studies using different measures for assessing the HLE (e.g., Foster et al, 2005;Melhuish et al, 2008;Bonifacci et al, 2021) have shown the impact of the HLE on children's outcomes. Rodriguez and Tamis-LeMonda (2011) used a measure for all aspects of the HLE, and found strong associations between the HLE and children's skills in receptive vocabulary and emergent literacy.…”
Section: Introductionmentioning
confidence: 99%